2003
DOI: 10.1172/jci200318200
|View full text |Cite
|
Sign up to set email alerts
|

A novel protective effect of erythropoietin in the infarcted heart

Abstract: Erythropoietin (EPO) has been shown to protect neurons from ischemic stroke, but can also increase thrombotic events and mortality rates in patients with ischemic heart disease. We reasoned that benefits of EPO might be offset by increases in hematocrit and evaluated the direct effects of EPO in the ischemic heart. We show that preconditioning with EPO protects H9c2 myoblasts in vitro and cardiomyocytes in vivo against ischemic injury. EPO treatment leads to significantly improved cardiac function following my… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(12 citation statements)
references
References 38 publications
(20 reference statements)
1
10
0
1
Order By: Relevance
“…However, rHuEPO treatment for 1 week also decreased macrophage infiltration, proinflammatory mediator (CRP), and profibrotic cytokine (TGF-β1 mRNA) expression without affecting Hb and Hct levels. This finding suggests that a direct effect of rHuEPO as well as improvement of hematopoiesis is responsible for protection against CsA-induced renal injury, which was previously demonstrated in the heart [14], CNS [15,16,17,18,19,20,21], and kidney [22,23,24]. …”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…However, rHuEPO treatment for 1 week also decreased macrophage infiltration, proinflammatory mediator (CRP), and profibrotic cytokine (TGF-β1 mRNA) expression without affecting Hb and Hct levels. This finding suggests that a direct effect of rHuEPO as well as improvement of hematopoiesis is responsible for protection against CsA-induced renal injury, which was previously demonstrated in the heart [14], CNS [15,16,17,18,19,20,21], and kidney [22,23,24]. …”
Section: Discussionsupporting
confidence: 67%
“…First of all, our study was focused on the effect of rHuEPO on apoptotic cell death since rHuEPO is a well-known anti-apoptotic agent against noxious or ischemic injury in various organs [14, 16, 18, 41, 42], and that apoptotic cell death plays a role in the pathogenesis of chronic CsA nephropathy [43,44,45]. The results of this study showed that rHuEPO significantly decreased the number of TUNEL-positive cells, which increased in CsA-treated rat kidneys.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sham-OP control animals (n = 9) underwent a similar procedure except that cryoprobes were not applied. Hearts of 6 cryoinfarcted animals were sectioned transaxially, and size of the infarcted LV area as a percent of total LV area was estimated to 32% ± 3% by triphenyltetrazolium chloride (TTC) staining ( Figure 1A) (22). There were no differences in infarct size between any subsequent groups (data not shown).…”
Section: Methodsmentioning
confidence: 96%
“…Several studies have recently demonstrated that recombinant human erythropoietin (EPO) was effective in the protection of the myocardium against ischemic injury [1,2,3,4,5,6,7]. A single injection of a high dose of EPO (1,000–5,000 U/kg), 12–24 h before ischemia-reperfusion, has been shown to confer preconditioning protection on the heart, preventing cardiomyocyte apoptosis and cardiac dysfunction [5, 8].…”
Section: Introductionmentioning
confidence: 99%